Common marmoset (Callithrix jacchus) as a primate model of dengue virus infection: development of high levels of viraemia and demonstration of protective immunity - Omatsu, Tsutomu; Moi, Meng Ling; Hirayama, Takanori; Takasaki, Tomohiko; Nakamura, Shinichiro; Tajima, Shigeru; Ito, Mikako; Yoshida, Tomoyuki; Saito, Akatsuki; Katakai, Yuko; Akari, Hirofumi; Kurane, Ichiro (Journal of General Virology, 2011)
Dengue virus (DENV) causes a wide range of illnesses in humans: dengue fever (DF), dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). Animal models that constantly develop high levels of viraemia are required for the development of protective and preventive measures. Common marmosets (Callithrix jacchus) demonstrated high levels of viraemia after inoculation with clinical isolates of four serotypes of DENV; in particular, over 106 genome copies ml−1 after inoculation with DENV-2. Non-structural protein 1 and DENV-specific IgM and IgG antibodies were consistently detected. The DENV-2 genome was detected in lymphoid organs including the lymph nodes, spleen and thymus, and also in non-lymphoid organs. DENV antigen was detected by immunohistochemistry in the liver and spleen from inoculated marmosets. Four marmosets were reinoculated with DENV-2 at 33 weeks after primary inoculation with DENV-2. The DENV-2 genome was not detected in any of these marmosets, indicating protection from a secondary infection. The results indicate that common marmosets are highly sensitive to DENV infection, and suggest that marmosets could be a reliable primate model for the evaluation of candidate vaccines.